2016
DOI: 10.3109/02713683.2015.1122810
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Omega 3 Fatty Acids in Rosacea Patients with Dry Eye Symptoms

Abstract: Rosacea patients with dry eye symptoms have significant improvement in symptoms, MGS, TBUT, and Schirmer score, following dietary intervention with O3FAs for 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 20 publications
0
75
0
6
Order By: Relevance
“…60 In fact, various animal and human studies have shown that omega 3 fatty acids (from which resolvins and protectins are derived) improved symptoms, signs, and inflammation associated with dry eye. [63][64][65][66][67] This effect is likely mediated through the biosynthetic process of omega fatty acids to resolvins and protectins. For example, neuroprotectin D1 (a product of docosahexaenoic acid (DHA)) was found to be as effective as DHA itself in improving corneal sensitivity and tear production and decreasing neutrophil infiltration after experimental nerve injury.…”
Section: Peripheral Sensitizationmentioning
confidence: 99%
“…60 In fact, various animal and human studies have shown that omega 3 fatty acids (from which resolvins and protectins are derived) improved symptoms, signs, and inflammation associated with dry eye. [63][64][65][66][67] This effect is likely mediated through the biosynthetic process of omega fatty acids to resolvins and protectins. For example, neuroprotectin D1 (a product of docosahexaenoic acid (DHA)) was found to be as effective as DHA itself in improving corneal sensitivity and tear production and decreasing neutrophil infiltration after experimental nerve injury.…”
Section: Peripheral Sensitizationmentioning
confidence: 99%
“…and a change in mean of 3.86 sec. Bhargava R. et al, 24 demonstrated a change in mean of 3.3 sec after 3 months treatment (325EPA+125DHA), Kangari et al demonstrated a change in mean of 1.7 sec after only a month's treatment. Although supplementation duration and its quantity varies in these studies, but there is a definite agreement about the beneficial effect of Omega 3 on this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Chinnery, et al found that Omega-3 supplementation imparts neuroprotective effects in the cornea sub-basal plexus which correlate with improvement in tear osmolarity [25]. In another study, rosacea patients showed improvement in symptoms, TBUT, Schirmer score and Meibomian gland score (MGS) with six months of Omega 3 supplementation [26]. An of ice-based study involving 1,419 patients in Spain found multiple bene its in dry eye sufferers utilizing a supplement that contained a combination of Omega-3 fatty acids, vitamins, minerals, and antioxidants [27].…”
mentioning
confidence: 90%